2011
DOI: 10.1111/j.1420-9101.2011.02400.x
|View full text |Cite
|
Sign up to set email alerts
|

Male inbreeding status affects female fitness in a seed‐feeding beetle

Abstract: Inbreeding generally reduces male mating activity such that inbred males are less successful in male–male competition. Inbred males can also have smaller accessory glands, transfer less sperm and produce sperm that are less motile, less viable or have a greater frequency of abnormalities, all of which can reduce the fertilization success and fitness of inbred males relative to outbred males. However, few studies have examined how male inbreeding status affects the fitness of females with whom they mate. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 76 publications
(145 reference statements)
0
34
0
Order By: Relevance
“…Eggs produced by inbred females may also be inferior at the stage of egg formation and provisioning. A previous study of C. maculatus found that inbred males produce fewer sperm (Fox et al 2012), so it is possible that inbred females experience similar problems during oogenesis, which could reduce both egg number and quality. Given our broad deÞnition of egg hatch, more detailed studies can reveal whether eggs laid by inbred females exhibit reduced embryogenesis, greater larval mortality before seed entry, or both (Fox et al 2007).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Eggs produced by inbred females may also be inferior at the stage of egg formation and provisioning. A previous study of C. maculatus found that inbred males produce fewer sperm (Fox et al 2012), so it is possible that inbred females experience similar problems during oogenesis, which could reduce both egg number and quality. Given our broad deÞnition of egg hatch, more detailed studies can reveal whether eggs laid by inbred females exhibit reduced embryogenesis, greater larval mortality before seed entry, or both (Fox et al 2007).…”
Section: Discussionmentioning
confidence: 96%
“…Periods of inbreeding may be common in these stored-product pests, because populations in stores of grain legumes are often founded by small numbers of individuals that emerge from Þeld-infested or transported seeds Credland 1995, Semeao et al 2012). Beetle populations in both the Þeld and laboratory exhibit substantial inbreeding depression for such traits as larval survival and development time, adult body size and lifespan, and male and female reproduction (Tran and Credland 1995;Fox et al , 2007Fox et al , 2012. Inbreeding depression for some beetle traits (e.g., survival) increases with the stressfulness of the environment (Fox andReed 2010, Fox et al 2011).…”
mentioning
confidence: 96%
“…Female mice ( Mus musculus musculus ) prefer the scent of outbred males to inbred males when both were infected with salmonella (Ilmonen et al 2009) and female mealworm beetles ( Tenebrio molitor ) prefer the scent of outbred males to inbred males (Pölkki et al 2012), but Aparicio et al (2001) found that males of spotless starling ( Sturnus unicolor ) with an intermediate level of heterozygosity were more successful in mating and reproduction than either of the extremes. These preferences may arise from reduced fitness in females who mate with inbred males instead of outbred ones as demonstrated in seed-feeding beetles (Fox et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Firstly, the costs of inbreeding these preferences for outbred males are unlikely to be driven by indirect (genetic) benefits, 60 because homozygosity is not heritable (Reinhold, 2002;Lehmann et al, 2007; but see Neff and 61 Pitcher, 2008; Nietlisbach et al, 2015). A more likely explanation is that inbreeding reduces 62 overall male quality and condition such that females gain fewer direct benefits from mating with 63 an inbred male (Fox et al, 2012). Direct benefits that may be affected by inbreeding include 64 sperm number and quality, nuptial gift size, and parental care ability (Fox et al, 2012 …”
mentioning
confidence: 99%
“…A more likely explanation is that inbreeding reduces 62 overall male quality and condition such that females gain fewer direct benefits from mating with 63 an inbred male (Fox et al, 2012). Direct benefits that may be affected by inbreeding include 64 sperm number and quality, nuptial gift size, and parental care ability (Fox et al, 2012 …”
mentioning
confidence: 99%